The Effect of Erythropoietin on Spatial Memory and Entorhinal Cerebrocortical Level of BDNF in Rat Model of Intrauterine Growth Restriction - Hamideh Rajabpour; Mohammad Amin Edalatmanesh (Islamic Azad University, 2018)
Introduction: Intrauterine Growth Restriction (IUGR) causes disruption for the central nervous system of fetus and is followed by cerebral cortex damage of neonates. This study aims to analyze the effects of erythropoietin (EPO) on spatial memory and brain-derived neurotrophic factor (BDNF) in entorhinal cortex of IUGR rat models. Methods: For IUGR induction, anterior uterine artery occlusion surgery is carried out on rats in embryonic day (ED) 14. From ED12, EPO are injected subcutaneously in 500, 1000 and 2000 IU/kg doses until the birth of their neonates. Spatial memory is analyzed by Morris water maze at postnatal day (PND) 30. Then, BDNF cerebral cortex level is estimated using ELISA. Differences between groups is analyzed with ANOVA and considered statistically significant at p ≤ 0.05. Results: A significant decrease is observed in spatial memory and BDNF cortex of untreated IUGR group in comparison with the control group (p ≤ 0.05). On the other hand, treatment of EPO improves spatial memory by increasing BDNF level in entorhinal cortex (p ≤0.05). Conclusion: The present study indicates that fetal growth restriction causes cognitive disorder in rat model. Consequently, expression of neurotrophic factors, such as cerebral cortical BDNF, will be decreased. Moreover, neuroprotective effects of EPO could ameliorate cognitive deficits in IUGR model.